Spray impact onto a hot solid substrate: Film boiling suppression by lubricant addition - Gajevic Joksimovic, Marija; Hussong, Jeanette; Tropea, Cameron; Roisman, Ilia V. (Frontiers in Physics, 2023)
Spray cooling of solid substrates is one of the methods used in various industrial processes such as forging, quenching or other metallurgical applications, electronics, pharmaceutical industry, medicine, or for cooling of powerful electrical devices. Spray cooling is governed by various hydrodynamic and thermodynamic processes, like drop impact, heat conduction in the substrate and convection in the spreading drops, and different regimes of boiling. The problem of modeling spray cooling becomes even more challenging if the liquid is multicomponent. The presence of components with various physicochemical properties (surfactants, binders, dispersed particles, etc.) can significantly affect the entire process of spray impact, as well as the outcome of the known cooling regimes and could lead to a formation of a thin deposited layer on the substrate. In this experimental study, spray impact onto a substrate, initially heated to temperatures significantly exceeding the liquid saturation point, is visualized using a high-speed video system. The heat transfer associated with spray impact is characterized using an array of thermocouples installed in a thick metal target. As a working fluid, a mixture of a distilled water and industrial white lubricant was used. It is observed that the presence of very small concentrations of lubricant augments the heat flux dramatically, particularly at high wall temperatures, at which usually film boiling is observed for spray cooling by using distilled water. Three main mechanisms leading to the increase of heat flux and shift of the Leidenforst point. They are caused by the significant viscosity increase of the evaporating lubricant solutions, by an increase of the substrate wettability and by the emergence of stable liquid sheets between bubbles, preventing their coalescence and percolation of the vapor channels.